Evaluating the effectiveness of the operation car repair enterprises (Transport systems and technologies, 2019)
Nowadays, the reliability of production systems for repairing freight cars is unsatisfactory. There is a constant decrease in the parametric characteristics of technological processes by time. As a result of the lack of efficient procedures for rolling stock renewal, insufficient implementation of advanced technologies and approaches to the organization of production, repair of freight cars is characterized by poor quality. Aging of fixed assets of enterprises, which takes place in crisis conditions with the provision of material and financial resources, contributes to the deterioration of the general situation in production.The most accessible and productive stage of development repair enterprises is the application of approaches to industrial logistics. But they need to maintain production systems at the specified levels of reliability and dynamic stability. Therefore, there is an urgent task of developing a method for evaluating their reliability.Modern cars repairs relate to a class of complex organizational systems that have variable parametric characteristics in time. The peculiarity of their functioning is the relative impossibility of treating failures in the system of categories "working-faulty" or "workable- unworkable".The article considers questions of the efficiency evaluation of production systems on the basis of determining the coefficient completeness of the renewal wagon resource. The specified characteristic allows us to determine the real state of the technological system and develop measures to optimize the production space.
Keywords: production system, dynamic stability, production efficiency, cars resources, reliability